1993
DOI: 10.1111/j.1365-2958.1993.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of spv virulence genes of the salmonella virulence plasmids

Abstract: SummaryGenes on an 8 kb region common to the virulence plasmids of several serovars of Salmonetia are sufficient to replace the entire plasmid in enabling systemic infection in animal models. This virulence region encompasses five genes which previously have been designated with different names from each investigating laboratory. A common nomenclature has been devised for the five genes, i.e. spv for salmonella Qlasmid virulence. The first gene, spvR, encodes a positive activator for the following four genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
221
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(226 citation statements)
references
References 69 publications
4
221
1
Order By: Relevance
“…PT11 strains in our study displayed distinct genetic properties which separated PT11 strains from both PT4 and PT8 groups, and included 70 genes in prophages ST104, P2, 186, ST64B, Gifsy-1 and Gifsy-2, and 76 nonprophage genes. Plasmid profiling (data not shown) revealed that PT11 strains possess a large plasmid (~80 kb), whereas strains from PTs 4, 6, 8 and 13a possess the virulence or spv plasmid (~58 kb) (Gulig et al, 1993). In addition, PFGE and MLST separated PT11 from other PTs.…”
Section: Discussionmentioning
confidence: 99%
“…PT11 strains in our study displayed distinct genetic properties which separated PT11 strains from both PT4 and PT8 groups, and included 70 genes in prophages ST104, P2, 186, ST64B, Gifsy-1 and Gifsy-2, and 76 nonprophage genes. Plasmid profiling (data not shown) revealed that PT11 strains possess a large plasmid (~80 kb), whereas strains from PTs 4, 6, 8 and 13a possess the virulence or spv plasmid (~58 kb) (Gulig et al, 1993). In addition, PFGE and MLST separated PT11 from other PTs.…”
Section: Discussionmentioning
confidence: 99%
“…The sp operon contains five genes (sp R, A, B, C, and D) [225] which are apparently highly conserved and are present on a family of serotype associated plasmids (SAP) commonly found in isolates of Typhimurium, Enteritidis, Dublin, Abortusovis, Choleraesuis and Gallinarum, these last four serotypes being HA or HR.…”
Section: The Virulence Plasmidmentioning
confidence: 99%
“…Also known as 38 or s , RpoS regulates expression of Ϸ10% of Escherichia coli genes (3), including katE and xthA, which encode hydroperoxidase II catalase and exonuclease III, respectively (4,5). In Salmonella enterica serovar Typhimurium, RpoS plays a major role in virulence by controlling expression of the spv plasmid genes (6,7), which govern Salmonella's growth rate in deep organs and are required for systemic infection in mice (8)(9)(10).…”
mentioning
confidence: 99%